Investigations on the Use of Different Ceramic Membranes For Efficient Oil-Field Produced Water Treatment - Ebrahimi, Mehrdad; Willershausen, Daniel; Shams-Ashaghi, Kikavous; Engel, Larisa; Placido, Laura; Mund, Peter; Bolduan, Peter; Czermak, Peter (My University, 2010)
Efficient performance of the combination of treatment processes for oilfield produced water generated from oil tank dewatering was investigated in the study presented below. By-produced wastewater is generated in significant quantity during exploitation of crude oil and gas from onshore and offshore production operations. This wastewater, commonly referred to as “produced water”, has distinctive characteristics, due to their organic and inorganic compounds. However, these characteristics change from well to well. The treatment process investigated here consists of a pre-treatment step utilizing microfiltration (0.1 and 0.2µm pore size filters) and/or a simulated batch dissolved air flotation (DAF), and a multistage post-treatment step utilizing cross-flow ultra- (0.05µm pore size and 20kDa molecular weight cut-off filters), and nanofiltration (1 and 0.75kDa MWCO filters). Filters used were ceramic membranes. To determine the separation capability of the processes described, various parameters, such as trans-membrane pressure varying from 0.5 to 2 bar, cross-flow velocity in the range of 0.6 to 1.3m/s, influent oil concentration ranging from 32 to 5420 parts per million (ppm) and different membrane cleaning methods used were investigated. The average permeate flux varied from 3.4 to 3300 l/h*m²*bar, total oil removal was up to 99.5% and total organic carbon removal reached 49%.
Keywords: Ceramic membrane; Oilfield; Produced water treatment; Microfiltration; Ultrafiltration; Nanofiltration; Simulated flotation; Membrane fouling; Permeate flux rate; Oil removal